Introducing Silverlight 4 - Ghoda, Ashish (Apress, 2012)
Microsoft Silverlight is a cross-browser, cross-platform, and cross-device plug-in for developing the next-generation, media-rich, interactive line-of-business (LoB) rich Internet applications (RIAs) in an agile and cost-effective way. In only nine months, after releasing Silverlight 3 in July 2009, Microsoft released Silverlight 4 in April 2010. The Silverlight 3 version introduced out-of-browser capabilities to work in the disconnected mode and access to local file systems, and it helped professionals to develop data-driven applications easily. Silverlight 4 introduced support to Windows 7 Mobile phones and highlighted demanded features, such as printing, documents integration, reporting, rich offline capabilities, and local devices to develop lineof- business (LoB) data-driven RIAs. The following are some of them: • Introduction of new and enhanced LoB RIA features, such as content printing capability, right-click context menus, drag-and-drop and copy-and-paste functionalities, notification windows, enhanced data controls and data binding features, full access to key boards, and integration with microphones and web cameras. • Silverlight applications with elevated trust as out-of-browser applications enable access to “My*” Folders for Windows (and on Mac mapped to related places). • Introduction of implicit theming and multicast UDP networking will help to improve the overall end-user experience. • Visual Studio 2010 enables the user interface development for Silverlight 4 (and Silverlight 3) RIAs and introduces better data binding and WCF RIA services integration with other enhancements to improve the development experience. • Silverlight 4 and Windows Phone development tools enable development of interactive Silverlight applications for Windows 7 Mobile Phone series.